Can We Build AI That Does Not Harm Queer People? - Weber, Sabine (Communications of the ACM, 2025)
This article examines the harmful information generated by artificial intelligence (AI) regarding aspects of the queer community with a focus on what can be done by computer scientists to prevent this problem. First, specific examples are detailed with a look at how they occur then a case study is presented. A fictitious software company’s text-to-image system and how software developers can work to overcome harm with direct and indirect methods is the focus on the case study.